Improving the quality of cast metal of pipeline valves by modification of dispersed inoculators - E. N. Eremin; G. N. Minnekhanov; R. G. Minnekhanov (Омский научный вестник)
The problem of improving the steel casting quality of pipeline valves made by electroslag casting is considered. An integrated approach to the melt preparation in electroslag casting is proposed including its deep deoxidation with a rare earth metal agent and introducing a modifying complex containing nanodispersed pyrocarbon particles, which forms a fine ferrite-pearlite structure with small globular nonmetallic inclusions located in the dendrite axes. This permits to produce castings made of wide class of steels with a high cold resistance level.